The Spirit of Tolerance from the Village: A Phenomenological Study of Multicultural Community in Balun, Gilimanuk, and Lingsar - Ida Bagus Putera Manuaba; Ni Wayan Sartini (MOZAIK HUMANIORA, 2022)
This study aims to describe the management of tolerance in the culture of a multicultural society. The culture the society studied is the culture of the multicultural society in Indonesia. This research is based on by a hypothetical idea that the village community wisely manages the diversity of local wisdom. The research objects selected were the society of the villages that are Balun-Lamongan, Gilimanuk-Jembrana), and Lingsar-West Lombok. This study uses a phenomenological perspective, with data collection techniques: interviews and observations. From this research, there are three findings. First, the attitude and spirit of tolerance in the multicultural society in the three villages studied have been cultivated in the form of local wisdom values ​​and become the cultural pattern of the society. Second, the communities in the three villages studied showed that their societies had more advanced experience in cultural harmonization in understanding the diversity of socio-cultural realities. Third, the people in the three villages studied used local wisdom in managing diversity which they did not understand as an obstacle, but as a potential to maintain the socio-cultural cohesion of the society.